Conflitos e dilemas dos gestores de organizações do terceiro setor em Uberlândia - MG - Mello, Angela (2007)
The third sector since its growth and full development has pointed to the need of new researches that may contribute for the understanding of this phenomenon. The characteristics of the organizations that compose this sector are presented in the academic studies as different from those pertaining to the first sector (government) and from the second sector (market). Considered divergent for their objectives, the third sector and the second sector organizations have in the actions of their managers the use of rationalities considered incongruous. Starting from this premise this study searched to identify the existence of quandaries and / or conflicts in managers of non-profit organizations, in order to reach organizational sustainability. Nineteen managers of non-governmental organizations in the city of Uberlândia - MG were interviewed using focused interviews. The research is characterized as descriptive. The found results demonstrate the existence of conflicts in both the individual and group spheres indicating, in the first case, that conflicts elapse mainly due to those administrative practices demanded for the organization to maintain itself. In the second case, the conflicts emerge due to the established social relations inside and outside these organizations. The studied cases reveals divergences in relation to other studies; however, more research is recommended for the deepening of the theme taking into consideration the diversification of organizations of this sector.